Legal Mechanism for Regulating the Labor of Healthcare Workers - Xeniya Kassymova; Yenlik Nurgaliyeva (Ital Publication, 2024)
Objective: This article aims to develop a mechanism for the legal regulation of the labor of healthcare workers in Kazakhstan based on comprehensive scientific issues analysis of ensuring the effectiveness of the legal regulation of employment relations, including by studying foreign experience in the countries of the Organization for Economic Cooperation and Development (OECD) and the Eurasian Economic Union (EAEU). Methods: Medical and pharmaceutical workers’ work regulations were analyzed to identify problems associated with personnel imbalance in Kazakhstan’s healthcare industry. The qualitative content analysis and the dialectical method of cognition formed the methodological basis of the study. Regulatory legal acts governing the issues of healthcare workers’ labor systems were units of analysis. Findings: The authors discovered certain flaws of legislative acts and their implementation about healthcare workers’ work. Improvement methods are proposed. Novelty:Theoretical novelty is represented by a topical approach of comprehensive analysis of the national labor legislation. Practical novelty includes proposals for the current employment legislation of Kazakhstan (unified regulation of working hours, unified regulation of employment contracts, upgrading remuneration system), including a new law draft, “Status of Medical and Pharmaceutical Workers”. Doi: 10.28991/ESJ-2024-08-04-014 Full Text: PDF